Association between weight status and body image perception among female adolescents in Terengganu - Rhehana Mohd Ayob,; Wee, Bee Suan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Body image is the picture of how our body is perceived and stored in our minds. During puberty, many changes occur in the body of adolescents. Often, a change in physical appearance has an impact on the levels of the body’s satisfaction. Thus, it is crucial to assess the body image among adolescents to ensure the wellbeing of both physical and mental health is at the optimal stage. Therefore, the present study aims to determine the body fat percentage of female adolescents. Then, to evaluate the association between weight status and body image perception. Lastly, to assess whether the attitudes towards body image are predictive of female adolescents’ weight status. This cross-sectional study was conducted among 198 female adolescents in Kuala Nerus, Terengganu. Anthropometric measurements included weight and height, and BMI was determined. Body composition was assessed by using Bio-electrical Impedance Analysis through Bodystat Quadscan 4000 instrument. Body image perception was measured using Stunkard’s Figure Rating Scale and Attitudes towards Body Image that was adapted from the Multidimensional Body Self Relation Questionnaire (MBSRQ). A total of 27.8% of female adolescents were overweight and 1.0% were obese by body fat. Among the female adolescents, 62.5% were dissatisfied with their body image, although 57.5% of them were in the normal weight category. Pearson’s Chi-Square test revealed there is an association between weight status and body image perception among female adolescents (p<0.045). Based on the Multiple Linear Regression Analysis, there is a significant linear relationship between attitudes towards body image, the domain of comparison of body shape, and BMI (p<0.005). Thus, for every 1 unit increase in the domain of comparison of body shape, there will be a 0.570 decrease in BMI. Comparison of body shape is a significant predicting factor for BMI. In conclusion, further study should be carried out to investigate the factors that can lead to the development of dissatisfaction with body image and the effects of getting negative body image in life of the adolescents during their adolescent’s phase.